(untitled) (Annual Transactions of the Nordic Rheology Society, 2025)
During well construction, control of drilling mud rheology is required at elevated temperature and pressure. Therefore, understanding the influencing factors on water-based mud (WBM) rheology characteristics, as one of the most commonly used drilling fluids, is essential to maintain firm control over the rheological properties of elevated temperature WBM. Due to the changing rheological properties of some additives at elevated temperatures, selecting appropriate additives for WBM is challenging. This study focuses on the behavior of a typical bentonite mud utilizing a state-of-the-art viscometer to measure drilling fluids properties at different concentrations of bentonite and temperatures. The sensitivity of the mud to shear stress at different temperatures and concentrations was examined. The experimental approach involved mixing distilled water with bentonite and conducting experiments, including preparation and hot rolling to simulate the aging of mud during circulation. Rheological properties of the mud were measured at various concentrations (8 and 12 g) across temperatures (10 to 90°C) and shear rates (5 to 1021 s-1) to identify patterns for predicting the mud behavior. The results show that the rate of shear stress increase is a strong function of temperature in the applied shear rate range. Plastic viscosity decreased with temperature, being highest at 10°C and lowest at 90°C. Additionally, temperature increase leads to increased yield stress. It is believed that at higher temperatures face to face repulsive electrostatic energy between particles is higher. Additionally, higher temperatures led to an increased yield stress due to stronger particle interactions. It is proposed that, as a result of these enhanced interactions at higher temperatures, a more robust gel structure would be formed. The experimental data closely fit the Herschel-Bulkley model, confirming its suitability for predicting bentonite mud behavior under varying temperatures and shear rates. This study provides a deeper understanding of how temperature and bentonite concentration influence the rheology of bentonite muds. Also, these findings highlight the complexity of maintaining mud rheology at elevated temperatures, as viscosity changes can affect mud stability and drilling efficiency. Moreover, it offers practical insights for optimizing bentonite concentrations to ensure efficiency in field applications for elevated temperature conditions.